Reconocimiento de enfermedades fungosas transmitidas por semilla en germoplasma de Brachiaria spp - García, S.X.; Pineda López, Benjamín (2000)
The Brachiaria germplasm collection maintained in CIAT, contains more than 700 accessions of 27 identified species. The process of regeneration and increase of germplasm is carried out in Popayán (2° 25 N; 76° 40 W) under field conditions. There is little available information about Brachiaria seed-borne fungal diseases, requiring phytopathological information to the reference, reason for the who was carried out the present study to establish the kind of fungi transmitted by seeds affecting the process of the increasing of the species Brachiaria brizantha, Brachiaria decumbens and Brachiaria jubata. For this research seed samples of B. brizantha, B. decumbens and B. jubata. harvested in Popayán during 1998 and the first semester of 1999, and conserved in the dryer of cold air were selected. The samples were conditioned properly and carried out them analysis of seed health in the laboratory using a blotter test and agar plate methods, and identification of the fungi by means of microscopical analysis. The gotten outputs showed that the used accesions of the three species of Brachiaria were affected by the fungi as Alternaria sp., Aspergillus sp., Curvularia spp., Chaetomium spp., Drechslera spp., Cladosporium spp., Epiccocum spp., Nigrospora spp., Penicillium spp., Phoma spp., and another unidentified fungi. The measured fungi incidence showed that Drechslera spp., and Phoma spp. were the high incidence fungi observed. In the B. brizantha species and B. decumbens met, in the analysis by means of humid camera, that the incidence of Drechslera spp. it was from the 11.25% and 9.14%, while for Phoma spp. it returned at 7.75% and 5.57%. In B. jubata the incidence of Phoma spp, it you was from the 8.1% and the of Drechslera spp. 1,3%. In the analysis by means of the agar plate method (PDA-Ac) for B. brizantha was determined that Dreschlera spp. and Phoma spp., showed an incidence of the 5,89% and 12.33%, of the 6.86% and 9.07% in B. decumbens and of the 0.3% and 5.6% for B. jubata, respectively. Pathogenicity test with Drechslera spp. and Phoma spp., which were the fungi with high incidence, caused severe symptoms in seedlings. The result of this study should be important for determining the risk of these fungi in the safe movement of Brachiaria germplasm.